New modelling tools for the human genome project: 1 A study of the Ogston regime for small analytes and 2 Models for solid phase DNA amplification - Mercier, Jean-Francois (University of Ottawa (Canada), 2004)
Now that the human genome project has been completed, the race is on to improve the existing sequencing techniques, or develop new ones, to allow affordable and reasonably quick personal DNA testing. This would help predict personal response to drugs and disease predisposition. The standard sequencing method is based on electrophoresis, which allows a sorting of molecules according to their size. In the first part of this thesis, I develop a new numerical method to rapidly obtain the continuum limit mobility of a migrating molecule, using results obtained on a lattice. I then use this technique to re-examine the theoretical foundation of the current model (the Ogston-Morris-Rodbard-Chrambach or OMRC model) used to describe the molecular size dependence of the electrophoresic mobility of small molecules during gel electrophoresis. I consider three-dimensional gels and electric field lines similar to the ones used in electrophoresis and show that the OMRC model could not reliably predict the mobility of a molecule in a gel. In the second part of this thesis, I present a computational study of a new technique that could be used to provide alternatives to electrophoresis-based sequencing. This technique, named solid phase DNA amplification, allows for the parallelization of DNA amplification (and ultimately, a new sequencing method). I use Monte Carlo and Brownian Dynamics simulations to model this new experimental technique. I show that it leads to a geometrical amplification of DNA molecules and sharp population size distributions.
Keywords: Biophysics, General.